2016
DOI: 10.1016/j.jmatprotec.2015.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Controlling hard zone formation in friction stir processed HSLA steel

Abstract: a b s t r a c tThe present study was undertaken to determine the effects of friction stir process conditions on mitigating the "hard zone" often present in FSW HSLA steels. The primary parameters investigated were travel speed, heat input, and cooling rates. The hard zone consists of primarily fine lath ferrite. There are strong linear correlations between the ferrite lath width, hardness of the hard zone, and weld cooling rate. The hard zone was eliminate at cooling rates below 20 • C s −1 in FSW HSLA-65.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 4 publications
2
18
0
Order By: Relevance
“…However, according to our numerical simulation, it is unlikely that such a significant difference in cooling rates exists in such a small distance. In addition, Nelson et al [15] reported that cooling rates below 20°C s −1 eliminated the presence of the hard zone, while we found the same microstructures up to around 45°C s −1 . Difference between our FSW modeling results and the open literature [14,15] is related to chemical composition of the steels, thermal and strain history before processing or welding, and welding parameters.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…However, according to our numerical simulation, it is unlikely that such a significant difference in cooling rates exists in such a small distance. In addition, Nelson et al [15] reported that cooling rates below 20°C s −1 eliminated the presence of the hard zone, while we found the same microstructures up to around 45°C s −1 . Difference between our FSW modeling results and the open literature [14,15] is related to chemical composition of the steels, thermal and strain history before processing or welding, and welding parameters.…”
Section: Discussionsupporting
confidence: 78%
“…In addition, Nelson et al [15] reported that cooling rates below 20°C s −1 eliminated the presence of the hard zone, while we found the same microstructures up to around 45°C s −1 . Difference between our FSW modeling results and the open literature [14,15] is related to chemical composition of the steels, thermal and strain history before processing or welding, and welding parameters. Therefore, taking into account the material flow and thermal history dependency on the metallurgical aspects of the workpiece [30], tool design, and type of material [4] is important to better interpret the produced microstructures and its evolution.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations